Application of Two-Tier Multiple Choice Assessment Equipped with Certainty of Response Index as a Misconception Diagnosis Instrument in Chemistry Learning - Cahyani, Nilamsari; Auliah, Army; Majid, Ahmad Fudhail (Jurnal Pendidikan Matematika dan Sains, 2024)
AbstractThis study aims to analyze misconceptions and diagnose the causes of misconceptions in learning chemistry on acid-base material experienced by high school students in the second year. The research method used is descriptive qualitative with a squental explanatory design. The research subjects consisted of all students of class XI IPA 2 SMA Hasanuddin Gowa. The research instruments used include diagnostic tests and interview guidelines. Data were collected through two-tier multiple choice diagnostic tests supported by CRI (Certainty of Response Index) and interviews. The results of the analysis showed the presence of misconceptions in all indicators of the acid-base concept, with an average percentage of misconceptions exceeding 20%. The highest level of misconception was found in the concept of pH in the environment (63.0%), while the lowest misconception was found in the concept of acid-base indicators (33.3%). Diagnosis of the causes of students' misconceptions includes students' lack of mastery of chemical representations, the existence of intuitive and associative thinking, and students' lack of interest in learning chemistry.Keywords: Misconception, two-tier multiple choice, CRI, acid-base.